Polar Icebreaker roles and U.S. future needs : a preliminary assessment - National Research Council (U.S.). Committee on the Assessment of U.S. Coast Guard Polar Icebreaker Roles and Future Needs; National Research Council (U.S.). Polar Research Board (Washington, D.C. : National Academies Press, 2005)
At the request of Congress in PL 108-334, the U.S. Coast Guard (USCG) provided funds to the National Research Council of the National Academies to establish the Committee on the Assessment of U.S. Icebreaker Roles and Future Needs. The Committee's Statement of Task charges it to provide a comprehensive assessment of the current and future roles of U.S. Coast Guard polar icebreakers in supporting U.S. operations in the Antarctic and the Arctic, including scenarios for continuing those operations and alternative approaches, the changes in roles and missions of polar icebreakers in the support of all national priorities in the polar regions, and potential changes in the roles of U.S. Coast Guard icebreakers in the Arctic that may develop due to environmental change. The Committee was asked to provide a brief interim report to highlight the most urgent and time-dependent issues, and this report fulfills that request. The Committee will provide a final report covering the full scope of its tasks and more detailed analysis in the late summer of 2006. In this interim report, the Committee describes present and expected future uses of the polar icebreakers (POLAR STAR, POLAR SEA, and HEALY) with respect to relevant U.S. Coast Guard missions in the Antarctic and the Arctic, including national defense, homeland security, support of economic activity, law enforcement, search and rescue, environmental protection, and the support of and conduct of science, as part of an overall demand for icebreaking services.
""Front matter""; ""Acknowledgments""; ""Contents""; ""Summary""; ""1 Introduction""; ""2 Rationale for a Continued U.S. Icebreaking Capability""; ""3 The U.S. Coast Guard Icebreaker Fleet""; ""4 Potential Influences on Future Needs for Icebreakers""; ""5 Findings and Recommendations""; ""References""; ""Appendix A Statement of Task""; ""Appendix B Biographical Sketches of Committee Members""
Includes bibliographical references.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Icebreakers (Ships); Ice breaking operations -- Polar regions; Ice caps; Oceanography; TRANSPORTATION -- Ships & Shipbuilding -- Pictorial; TECHNOLOGY & ENGINEERING -- Marine & Naval; Ice breaking operations; Icebreakers (Ships); Polar regions; Electronic books